First record of Vallonia costata (O. F. Müller, 1774) (Gastropoda, Eupulmonata, Valloniidae) from British Columbia, Canada, confirmed by partial-COI gene sequence - Annegret Nicolai; Robert G. Forsyth (Check List, 2019)
The minute terrestrial snail Vallonia costata (O. F. Müller, 1774) is reported for the first time from the province of British Columbia, Canada. The identification was based on shell morphology and confirmed by COI gene data. This species is presumed to be introduced to the province.